The Benefits of the Cold and Domestication: A New Understanding of Human-Animal Partnerships for Thriving in Extreme Environments - Stammler, Florian; Takakura, Hiroki (Arctic Worlds, 2025)
This book explores cooperation between humans and animals in extreme environments and contends that understanding domestication is crucial to explaining how life is possible in such conditions. The chapters draw on work from anthropology, genetics, law, and geography, with a range of ethnographic case studies from cold environments. The contributors offer new evidence for rethinking the dichotomy of trust vs domination previously used to characterize human-animal relations. They show how humans and animals partner for survival, and how a cold environment does not merely threaten existence but rather creates opportunities. Domestication is presented as a continuous, mutually beneficial human-animal relationship of becoming familiar with each other and the surrounding environment, which can lead to a symbiotic partnership of multiple agents for adapting to changes including a warming climate. This volume will be relevant to scholars from anthropology, geography, and related disciplines interested in human-animal relations, ecology, and the environment, particularly in the North.